Flow characteristics and mechanics of vortex-induced vibration of cable model under passive–suction–jet control. (January 2023) - Min, Xiang-Wei; Chen, Wen-Li; Guo, Yan-Jiao; Chen, Changlong
Abstract: The control effect and mechanism of a passive–suction–jet control scheme on the vortex-induced vibration (VIV) of a stay-cable model were experimentally investigated in this study. The vibration responses and flow characteristics of an elastically mounted rigid cable model under passive–suction–jet control were measured at damping ratios ( ξ ) of 0.11%–0.29% and Reynolds numbers ( Re ) of 12700–29200. The control scheme was realized using specially designed pipes that could spontaneously produce jet flow from the holes on the leeward surface of the pipes. The results of the vibration response and lock-in region show that the passive–suction–jet control was effective in suppressing cable VIV, especially at ξ ≥ 0.17%. The evolution of the wake vortices at a low damping ratio ( ξ = 0 . 11 % ) and high damping ratio ( ξ = 0 . 17 % ) was discussed to study the vortex dynamics of the cable model subjected to VIV. The control mechanism of the pipe was also explored in terms of swirling strength distributions, streamlines, and velocity profiles in the wake field. The jet flow from the pipes was unsteady and formed periodic small-scale vortices at low damping ratios. At a high damping ratio, the jet flow was a steady flow and could suppress VIV more effectively.